Growth, Savings, Financial Markets and Markov Switching Regimes - Tor Jacobson; Thomas Lindh; Anders Warne (Sveriges Riksbank, 1998)
We report evidence that the relation between the financial sector share, private savings and growth in the United States 1948-1996 is characterized by several regime shifts. The finding is based on vector autoregressions on quarterly data that allow for Markov switching regimes. The evidence may be interpreted as support for a hypothesis that the relation between financial development and growth evolves in a stepwise fashion. Theoretical models where financial market extensions entail fixed costs imply such stepwise patterns. The estimated variable relations are roughly consistent with the patterns to be expected from such models, although our data do not admit definite conclusions. The timing of the shifts coincides with regulatory changes and changes in the financial market structure.
Keywords: C32; E44; O16; O51; 330; Financial development; Growth; Markov switching; Savings; Vector autoregression